Political Texts of the Early ХХ Century: Communicative-Discursive Features - T. P. Rogozhnikova (Научный диалог)
The results of a discursive analysis of political texts of the period 1903-1906 are presented. Particular attention is paid to the methodology for the study of political discourse in a historical perspective. The question is raised about the various spheres of the generation of political texts and their existence, participants in political communication, their socio-political affiliations. A discursive analysis of texts is carried out on the basis of a number of signs: authorship, targeted political text, communication strategies and tactics. It shows the actualization in the texts of opposing political parties of agonism as a specific property of political communication, the peculiarity of the implementation of agonism in the strategies and tactics of the authors: the monarchist and representatives of radical left parties. The classification of tactics that implement the strategy of discredit and the strategy of the struggle for power is given. The tactics of solidarity, appeal to values and opposition are indicated as dominating in the speeches of Bishop Gabriel. In the proclamations tactics of accusation, negative assessment and a call for a struggle for power are indicated. The character of the dependence of language means (including those from the arsenal of other types of discourse) on the nature of communicative tactics is determined. Textual combinations of communicative tactics are considered. Historical political texts are investigated in the communicative-discursive aspect.